¿How human-centered design can contribute to the creation of public goods for producers in Guatemala? - Christen, Roberto; Bonilla, Melissa; Zapata, Emmanuel; Müller, Anna (2024)
This paper introduces a systematic documentation initiative to capture success stories of Human-Centered Design (HCD) implementation across CGIAR projects. As part of an ongoing series showcasing the CGIAR HCD team's impact, this case study examines the redesign of agroclimatic bulletins in partnership with the Instituto Privado de Investigación sobre Cambio Climatico (ICC)in Guatemala. The study demonstrates how participatory co-design methods transformed traditional climate information delivery into more accessible and actionable formats for farmers. Beyond the tangible improvements in bulletin design, the process fostered stronger stakeholder partnerships and shifted researcher perspectives on user engagement. This case, exemplifying how HCD methodologies enhance both product development and organizational relationships, contributed to establishing agroclimatic information as a public good. As part of a growing portfolio, this documentation series aims to demonstrate HCD's strategic value within agricultural research and development projects, providing valuable insights for research institutions seeking to integrate and document user-centered approaches in their work.